Progressive changes in chromatin structure and DNA damage response signals in bone marrow and peripheral blood during myelomagenesis - Gkotzamanidou, M.; Terpos, E.; Bamia, C.; Kyrtopoulos, S.A.; Sfikakis, P.P.; Dimopoulos, M.A.; Souliotis, V.L. (Leukemia, 2014)
The molecular pathways implicated in multiple myeloma (MM) development are rather unknown. We studied epigenetic and DNA damage response (DDR) signals at selected model loci (N-ras, p53, d-globin) in bone marrow plasma cells and peripheral blood mononuclear cells (PBMCs) from patients with monoclonal gammopathy of undetermined significance (MGUS; n=20), smoldering/asymptomatic MM (SMM; n=29) and MM (n=18), as well as in healthy control-derived PBMCs (n=20). In both tissues analyzed, a progressive, significant increase in the looseness of local chromatin structure, gene expression levels and DNA repair efficiency from MGUS to SMM and finally to MM was observed (all P<0.002). Following ex vivo treatment with melphalan, a gradual suppression of the apoptotic pathway occurred in samples collected at different stages of myelomagenesis, with the severity and duration of the inhibition of RNA synthesis, p53 phosphorylation at serine15 and induction of apoptosis being higher in MGUS than SMM and lowest in MM patients (all P<0.0103). Interestingly, for all endpoints analyzed, a strong correlation between plasma cells and corresponding PBMCs was observed (all P<0.0003). We conclude that progressive changes in chromatin structure, transcriptional activity and DDR pathways during myelomagenesis occur in malignant plasma cells and that these changes are also reflected in PBMCs. © 2014 Macmillan Publishers Limited. All rights reserved.
Keywords: DNA damage response signals; epigenetics; monoclonal gammopathy of undetermined significance; multiple myeloma; myelomagenesis; Smoldering multiple myeloma